2000
DOI: 10.1021/jm990483l
|View full text |Cite
|
Sign up to set email alerts
|

Phosphinic Derivatives as New Dual Enkephalin-Degrading Enzyme Inhibitors: Synthesis, Biological Properties, and Antinociceptive Activities

Abstract: The development of dual inhibitors of the two zinc metallopeptidases, neprilysin (neutral endopeptidase) and aminopeptidase N involved in the inactivation of the opioid peptides, enkephalins, represents an attractive physiological approach in the search for new analgesics devoid of the major drawbacks of morphine. Phosphinic compounds, corresponding to the general formula H(3)N(+)-CH(R(1))-P(O)(OH)-CH(2)-CH(R(2))-CONH-CH(R(3))-COO(-), able to act as transition-state analogues and to fit the S(1), S(1)', and S(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 34 publications
2
70
1
9
Order By: Relevance
“…The decrease in inhibition of cAMP accumulation clearly reflected hDOR desensitization and not opioid agonist degradation because addition of freshly prepared agonist in the preincubation medium after 30-(30 ؉ agonist) or 120-min (120 ϩ Leu or Met) exposure could not restore the initial inhibitory action of agonists. Moreover, preincubation of SK-N-BE cells for various times (10, 30 min or 24 h) at different concentrations (10-to 100-fold the K i of the inhibitor) of RB3020, described as a dual enkephalin-degrading enzyme inhibitor (Chen et al, 2000), did not significantly affect enkephalins-mediated desensitization (ANOVA) (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…The decrease in inhibition of cAMP accumulation clearly reflected hDOR desensitization and not opioid agonist degradation because addition of freshly prepared agonist in the preincubation medium after 30-(30 ؉ agonist) or 120-min (120 ϩ Leu or Met) exposure could not restore the initial inhibitory action of agonists. Moreover, preincubation of SK-N-BE cells for various times (10, 30 min or 24 h) at different concentrations (10-to 100-fold the K i of the inhibitor) of RB3020, described as a dual enkephalin-degrading enzyme inhibitor (Chen et al, 2000), did not significantly affect enkephalins-mediated desensitization (ANOVA) (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…In a similar way, Roques et al [77] reported the synthesis of the phosphinic pseudopeptide (R,S,S)-81, which proved to be a potent dual inhibitor of the zinc metallopeptidases neprilysin and aminopeptidase N. For this purpose, the Michael addition of N-Cbz alanine H-phosphinic acid (R)-66c obtained by resolution [72], to ethyl p-bromobenzylacrylate followed by a Suzuki coupling using phenylboronic acid and subsequent alkaline hydrolysis of the ethyl ester, gave the C-phosphinic acid derivative 79 in 75% yield, which by the coupling with (S)-alanine methyl ester afforded the tripeptide 80 in 59% yield. Finally, the saponification of the methyl ester followed by the cleavage of the N-Cbz bond with BBr 3 and the semipreparative HPLC purification, provided the enantiomerically pure phosphinic pseudopeptide (R,S,S)-81 in 92% yield (Scheme 34).…”
Section: Scheme 32 Synthesis Of the C-phosphinic Acid 75 And Its Actmentioning
confidence: 79%
“…The alkylation of diethyl ethoxycarbonylmethylphosphonate (17) was described using sodium hydride in the glyme [20][21][22][23][24], DMF [25][26][27], diethyl ether [28], DMSO [29] or THF [30]. Others used potassium tert-butylate [31][32][33][34][35] or potassium tert-butylate/sodium iodide [36] in DMSO.…”
Section: Alkylation Of Diethyl Ethoxycarbonylmethylphosphonate Under mentioning
confidence: 99%
“…A widely used method for the alkylation of tetraethyl methylenebisphosphonate (27) applies NaH as the base in toluene [48][49][50]. In other methods, sodium in ether [51] or potassium in xylene [52] were used.…”
Section: Alkylation Of Tetraethyl Methylenebisphosphonate and Bis(dipmentioning
confidence: 99%
See 1 more Smart Citation